Parametric Study on Efficiency of Archimedes Screw Turbine - C. Zafirah, Rosly; Ummu Kulthum, Jamaludin; Nurul Suraya, Azahari (Asian Research Publishing Network (ARPN), 2016)
Production of electrical power through the use of the gravitational force and flowing water or electricity generated by power derived from the potential energy and running water is called hydroelectricity. The subject study is conducted to identify the potential parameters and desirable design for Archimedes Screw Turbine that has high power efficiency. Therefore, computational fluid dynamics (CFD) methods are used. By applying some boundaries condition such as steady state flow condition, isentropic flow and isothermal temperature, the simulation of water flow in the screw turbine can be shown and can be analyzed. This study shows that the higher number of helixes will decrease the efficiency of the screw turbine. Any modification in the design of the screw runner blade can be analyze for further study.